La población en la era de la información. De la transición demográfica al proceso de envejecimiento - Canales Cerón, Alejandro I. (El Colegio de México A.C., 2001)
Towards the end of the 20th century, changes in demographic dynamics led to a new system for the quantitative and social reproduction of society. By this the author means the changes in the demographic structure resulting from the population's aging process, as well as the emergence of various problems linked to gender, intergenerational and ethnic relations among others, which, in the framework of economic and cultural globalization, appear to involve the world population as a whole. In this respect, this article presents a conceptual review of demographic discourse in modern society, in the light of the theoretical and methodological challenges raised in the demographic structure on the threshold of the information era.